Managing the customer experience: a beauty retailer deploys all tactics. Issue 1 (26th November 2018) - Koetz, Clara
Abstract : Purpose: This paper aims to analyze the concept of customer experience in the marketing literature, identify its dimensions and applications in retail companies and integrate it with the concepts of touchpoints and consumer journey; some correlated concepts, such as customer delight and engagement, are also clarified, and an example of best practice customer experience management, using the beauty product company Sephora as a reference is provided. Design/methodology/approach: The case analysis was based on an examination of available public documents, such as press articles, case studies and the content of beauty blogs and social media (Facebook and YouTube) from 2014 to 2017; Sephora's social media communities (Beauty Talk, The Glossy and Sephora TV); the company's website and mobile application; and physical stores and Sephora Flash (a mix of a physical and digital store). Findings: Four categories emerged from the analysis, namely, to provide an enhanced omni-channel shopping experience, to reward loyalty and to bond with customers, to promote social shopping experiences and to delight customers. Practical implications: The study results provide retail managers important insights for maximizing customer experience across different touchpoints and throughout the whole journey to increase customer engagement and loyalty. Originality/value: The paper provides clear theoretical and practical basis for customer experience management, based on an analysis of the concepts of customer experience, delight and engagement, as well as a case analysis of a company that excels in this area.